Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV SONNE during cruise SO201/1b - Reinhard Werner; Maxim V Portnyagin; Anne-Cathrin Wölfl (PANGAEA, 2023)
Multibeam bathymetry raw data was recorded in the Pacific during cruise SO201-1b that took place between 2009-06-09 and 2009-07-06. The data was collected using the ship extquotesingles own Kongsberg EM 120.